Sex-related differences in joint-angle-specific hamstring-to-quadriceps function following fatigue. Issue 8 (14th September 2019) - El-Ashker, Said; Allardyce, Joanna M.; Carson, Brian P.
Abstract: The purpose of this study was to examine the effect of fatiguing exercise on sex-related differences in the function of hamstring and quadriceps muscles at several angular velocities and joint angles. Physically active participants (50 male: 28.7 ± 4.5y, 1.82 ± 0.07 m, 82.3 ± 6.87 kg; 50 female: 27.0 ± 5.8y, 1.61 ± 0.08 m, 68.75 ± 9.24 kg) carried out an isokinetic assessment to determine concentric and eccentric torques during knee extension and flexion actions at three different angular velocities (60/180/300°/s). The H/QFUNCT was calculated using peak torque (PT) values at 3 different joint-angle-specific (15°, 30° and 45° of knee flexion). A repeated measures analysis of variance (ANOVA) was used to compare within group results. Between group comparisons of sex-related differences were assessed by independent T-tests. Fatiguing exercise in males resulted in a decrease in H/QFUNCT ratios for each angle of knee flexion at both 60°/s and 300°/s angular velocities ( p < 0.05). In females, significant decreases in H/QFUNCT ratios were observed following fatiguing exercise for each angle of knee flexion and angular velocity ( p < 0.01). Significant differences in H/QFUNCT ratios following fatiguing exercise were evident between males and females at each joint angle and angular velocity ( p < 0.01). These findings indicate sex related differences in H/QFUNCT ratios following fatiguing exercise. Females have greater reductions in torque and H/QFUNCT ratios following fatigue than their male counterparts. This potentially exposes females to higher risks of injury, particularly when fatigued. Practitioners should attend to the imbalance in fatigue resistance of hamstring and quadriceps function, particularly in female athletes.